3d (Co and Mn) and 4d (Ag) Transition Metal-Doped ZnO Nanoparticles Anchored on CdZnS for the Photodegradation of Rhodamine B - Ann Wangari Mureithi; Chen Song; Thi Kim Tran Tran; Hawi N. Nyiera; Xueni Huang; Tejas S. Bhosale; Abiodun Daniel Aderibigbe; Ranjana Burman; Steven L. Suib; Jing Zhao (Crystals, 2023)
The construction of a heterojunction by coupling two semiconductor photocatalysts with appropriate band positions can effectively reduce the recombination of photogenerated charge carriers, thus improving their catalytic efficiency. Recently, ZnO photocatalysts have been highly sought after in the synthesis of semiconductor heterostructures due to their wide band gap and low conduction band position. Particularly, transition metal-doped ZnO nanoparticles are attractive due to the additional charge separation caused by temporary electron trapping by the dopant ions as well as the improved absorption of visible light. In this paper, we compare the effect of doping ZnO nanoparticles with 3d (Co and Mn) and 4d (Ag) transition metals on the structural and optical properties of ZnO/CdZnS heterostructures and their photocatalytic performance. With the help of scanning electron microscopy, the successful anchoring of doped and undoped ZnO nanoparticles onto CdZnS nanostructures was confirmed. Among the different heterostructures, Ag-doped ZnO/CdZnS exhibited the best visible-light-driven degradation of rhodamine B at a rate of 1.0 × 10−2 min−1. The photocurrent density analysis showed that AgZnO/CdZnS has the highest amount of photogenerated charges, leading to the highest photocatalytic performance. The reduction in the photocatalytic performance in the presence of hole scavengers and hydroxyl radical scavengers confirmed that the availability of photogenerated electrons and holes plays a pivotal role in the degradation of rhodamine B.